Hubungan kepatuhan asupan natrium dan konsumsi obat terhadap tekanan darah penderita hipertensi di wilayah Puskesmas Cibeber Kota Cilegon - Lukiah; Agestika, Lina; Jennie, Renan Prasta (UHAMKA PRESS, 2024)
Hypertension is one of the most common and chronic non communicable diseases. Continuous hypertension can disrupt blood flow in the kidneys, heart and brain. Efforts used to treat hypertension are pharmacological therapy (anti-hypertension drugs) and non-pharmacological therapy (one of which is reducing sodium consumption). This study aims to determine the relationship between intake natrium adherence and drug consumption on blood pressure of hypertensive patients in the Cibeber Community Health Center, Cilegon City. This study used an analytic observational method with a cross sectional design. The sampling technique used consecutive sampling techniques with a subject size of 77 people. The instruments used were the 2x24 hour food recall and Morisky Medication Adherence Scale (MMAS-8). The results of the spearman rank analysis test concerning the relationship between intake natrium adherence and blood pressure, namely not having a significant. There is realtioship between intake natrium adherence and systolic blood pressure is a p-value of 0,426 (p>0,05) while the relationship between intake natrium adherence and diastolic blood pressure is 0,303 (p>0,05). The results of the spearman rank analysis test regarding the relationship between intake natrium adherence to drug consumption and pressure, namely having a significant. The relationship between drug comsumption adherence and systolic blood pressure is a p-value of 0,001 (p<0,05) while the p-value of the relationship between drug comsumption adherence and diastolic blood pressure is 0,009 (p<0,05).